Адаптивні бази знань для систем підтримки прийняття рішень: підходи та моделі - Лихова, А. Г. (ХНУРЕ, 2025)
This research focuses on the development of adaptive knowledge bases for decision support systems (DSS). Special attention is given to the integration of ontological and problem-oriented approaches to improve the flexibilІТy and efficiency of knowledge structuring. The proposed framework provides an adaptable and structured foundation, enhancing decision-making capabilІТies in rapidly changing environments.
Keywords: адаптивна база знань; система підтримки рішень